Class II Division 2 Subdivision Malocclusion in an Adult Patient treated with the Forsus Fatigue-resistant Device placed Unilaterally - Oscar Mario Antelo; José Antonio Bósio; Armando Yukio Saga; Thiago Martins Meira; Orlando Motohiro Tanaka (Wolters Kluwer Medknow Publications, 2019)
Treatment of Class II subdivision malocclusion is challenging, and orthodontists frequently struggle to determine the choice of treatment. Several treatment modalities have been proposed for correcting these types of malocclusion. Thus, the aim of this case report is to present dentoalveolar and facial outcomes achieved using an unilateral Forsus fatigue-resistant device combined with fixed appliances in an adult female patient presenting with Class II subdivision malocclusion. Treatment outcome was effective producing dental esthetics and functional positive stable results after 3-year, 2-month follow-up.